Pemulihan Perekonomian Indonesia Melalui Digitalisasi UMKM Berbasis Syariah di Masa Pandemi Covid-19 - Moh. Musfiq Arifqi; Dedi Junaedi (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2021)
The Sharia MSME digitization activities are one of the alternatives for recovering Indonesian economy in Covid-19 pandemic. MSME is the community economic activities which are able to provide some opportunities to overcome the community economy. Currently, the MSME activities in Indonesia, which are predominantly by Muslim community, are faced with technological developments in increasing the productivity of their businesses. This requires a lot of strategies and innovations to rise these activities. Library research approach is used by researchers to examine in depth through searches on sources, exactly books, journals, news or other works that are considered. So this research is including to descriptive qualitative research. The results showed that digitizing sharia MSME was one of the efforts to increase the Indonesian economy in Covid-19 pandemic. The digitization of Islamic MSMEs has opportunities and challenges. The opportunity of this activities will be easier to appay it, both in production, distribution and consumption. The challenge is faced with the lack of human resources in accessing technology.